PENGARUH KECAKAPAN LITERASI DIGITAL TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN DI KABUPATEN GOWA - Surya Dharma (Universitas Muhammadiyah Surakarta, 2022)
This research was conducted with the aim of knowing the effect of digital literacy skills on the performance of Vocational High School teachers. The population in this study were all teachers who were civil servants at the State Vocational High School in Gowa Regency, totaling 238 teachers. The proportional random sampling technique was carried out in obtaining a research sample of 70 teachers who had previously used the slovin formula in determining the minimum number of research samples. questionnaire is an instrument in this research which in its development process is tested for content validity using the Gregory formula, construct validity using a confirmatory factor analysis (CFA) technique with a maximum likelihood approach, as well as testing the reliability of the instrument using the Cronbach alpha formula which produces a reliability coefficient value of 0.98 for the teacher's digital literacy skill instrument and a reliability coefficient value of 0.95 for the teacher's performance instrument. Simple linear regression technique was used to analyze the data obtained. The results of the study reveal that there is a positive and significant effect of digital literacy skills on the performance of Vocational High School teachers, and the contribution or influence of digital literacy skills on teacher performance is 39%.